Using Simulation Games to Teach History to Students Using Paradigm of Cultural-Historical Psychology - Nurgaliyeva, A.M.; Nourgaliev, K.A. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2024)
The article explores strategies for enhancing the effectiveness of training by fostering student engagement and motivating participation. The use of game-based techniques aims to boost students' motivation toward the material being studied. This approach is grounded in the principles of cultural and historical psychology as articulated by L.S. Vygotsky. It offers a theoretical framework for understanding differences not only in intercultural psychology but also in intertemporal psychology, as it enables the examination of psychological phenomena within specific historical, social, and cultural contexts. The article highlights the search for methods to increase motivation and the development of students' subjectivity and positionality. It provides examples of dialogue simulation games used in training, including historical reconstructions, mock trials, cultural immersion, and the Reacting to the Past initiative. Additionally, the article discusses the technologies involved in the preparation and implementation of these activities. This article provides an overview of research focused on the relationship between games and education. It highlights that participation in such games enhances both general and specialized skills and abilities among students, fosters a positive attitude toward learning, and deepens respect for history as a discipline. This approach allows for a theoretical understanding of facts grounded in historical context, helping to overcome the schematism and empiricism often associated with traditional school education. The methodology of simulation games enables students to explore the differences between the present and the past. These games encourage students to recognize and understand the unfamiliar realities of history, as well as the diverse ways of thinking that characterized people from different eras and cultures. The article concludes that well-designed educational games significantly increase the likelihood of achieving desired educational outcomes and contribute to the overall improvement of quality in higher education. The experiences shared regarding the use of role-playing or simulation games illustrate the potential of cultural-historical psychology as a valuable resource in history education. В статье рассматриваются возможности повышения эффективности обучения с помощью инициации активности учащихся и мотивирования их к участию в обучении. Игровая методика направлена на повышение мотивации учащихся к изучаемому материалу. В основу осмысления материала положены идеи культурно-исторической психологии Л.С. Выготского. Она дает теоретическую основу для объяснения различий не только межкультурных психологических, но и межвременных психологических, поскольку позволяет изучать психологические явления в конкретных исторических, социальных и культурных контекстах. Отмечены поиски способов повышения мотивации, становления субъектности и субъектной позиции у учащихся. Приведены примеры использования диалоговых имитационных игр в обучении: исторические реконструкции, имитационные судебные процессы, культурное погружение, Reacting to the Past. Рассмотрены технологии их подготовки и проведения. Дается обзор работ, посвященных изучению связи между играми и образованием. Отмечается, что участие в подобных играх укрепляет общие и специальные умения и навыки у студентов, положительное отношение к учению, углубляет уважение к истории как науке. При этом создается возможность теоретического отношения к фактам на базе исторической конкретности, преодоления схематизма и эмпиризма в знаниях и мышлении, порожденных школьным образованием. Методика имитационных игр предлагает студентам возможность обдумать различия между настоящим и прошлым. Подобные игры побуждают учащихся распознавать и осмысливать незнакомую реальность прошлого и различные способы мышления людей прошлых эпох и других культур. Делается вывод о том, что хорошо продуманные обучающие игры повышают шансы на достижение намеченных результатов, способствуют повышению качества обучения в высшей школе. Описанный в статье опыт использования разыгрывания или имитационных игр демонстрирует перспективность использования культурно-исторической психологии как важного ресурса в преподавании истории.